Assessment of variations in particular immunological and biochemical markers in rats under a standard and non-standard lifestyle: Immunological and biochemical markers in rats under a standard and non-standard lifestyle - Hama sheikh, Kardo Ibrahim; Khezri, Shiva; Farhan Shallal, Ahmed (Iranian Journal of Pharmaceutical Sciences, 2024)
This investigation aimed to assess the influence of vitamin D3 and calcium on certain immunological and biochemical factors in rats. Forty-eight male rats were assigned to eight distinct groups. There were two main groups. The first group had standard Diet-Fed rats (Vit. D3, Ca+2, Vit. D3, and Ca+2, Sunlight, and Fasting). The second group had high-fat diet-fed rats (HFD and HFD with Vit. D3 and Ca+2), also compared to the control group. The administration of calcium and vitamin D supplements lasted for six weeks. The levels of vitamin K, IL-10, TNF-α, IgM, and Osteocalcin were determined by applying ELISA. The administration of Vitamin D and calcium has been observed to significantly increase Vitamin D, Vitamin K, and Osteocalcin levels in the rats fed on the typical diet. In contrast, sunlight exposure and fasting for the same duration did not substantially impact serum vitamin D and Osteocalcin in rats fed a normal diet. Additionally, a significant reduction in the concentration of Vitamin K in the serum was detected in the experimental rats fed on a normal diet and subjected to sunlight and fasting. The administration of HFD for six weeks was found to provoke hyperglycemia in experimental rats. However, it did not elicit any significant influence on the concentration of vitamin D, vitamin K, and osteocalcin. Furthermore, using calcium and vitamin D for six weeks negatively impacted immune disturbances in rats consuming a normal diet (ND) or HFD by regulating anti-inflammatory cytokine (IL-10) secretion.